2001
DOI: 10.1002/ar.10016
|View full text |Cite
|
Sign up to set email alerts
|

Porcine enamel matrix derivative enhances trabecular bone regeneration during wound healing of injured rat femur

Abstract: To elucidate the effects of enamel matrix derivative (EMD: Emdogain) on bone regeneration in rat femurs after drill-hole injury, defects in bone were filled with either EMD or its carrier, PGA, as control. On postoperative days 4 to 28, dissected femurs were examined by means of various morphological approaches. In both experimental groups, formation of trabecular bone, which was immunostained for bone sialoproteins (BSP), had occurred in the medullary cavities at cylindrical bone defects on Day 7 postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 26 publications
2
45
1
1
Order By: Relevance
“…The key components improving new bone formation in the present study were the effects of enamel matrix proteins which have been shown to affect new bone formation under various models and also utilizing various carrier systems [20,[31][32][33][34][35]. In a classical study by Boyan et al, it was shown that although EMD does not possess osteoinductive potential, it possessed osteopromotive benefits when it is combined with active demineralized freeze-dried bone allografts (DFDBA) and resulted in enhanced bone induction [31].…”
Section: Discussionmentioning
confidence: 81%
“…The key components improving new bone formation in the present study were the effects of enamel matrix proteins which have been shown to affect new bone formation under various models and also utilizing various carrier systems [20,[31][32][33][34][35]. In a classical study by Boyan et al, it was shown that although EMD does not possess osteoinductive potential, it possessed osteopromotive benefits when it is combined with active demineralized freeze-dried bone allografts (DFDBA) and resulted in enhanced bone induction [31].…”
Section: Discussionmentioning
confidence: 81%
“…It enhances the osteoinductive potential of the graft material, due in part to its osteoconductive properties, but a threshold concentration is required. The latter conclusion was further supported in a morphological study in which the effect of locally applied EMD on bone and medullary regeneration was evaluated with the use of rat femurs in a drill-hole injury model (Kawana et al, 2001). The created defects were filled with either EMD (test group) or its carrier, PGA (control group).…”
Section: (Ii6) In Vivo Studies (Ii61) In Vivo Animal Studiesmentioning
confidence: 84%
“…While Emdogain has been reported to possess osteopromotive effects on bone healing during repair of bone defects [51,52], other studies have indicated that Emdogain is not truly osteogenic in terms of its ability to induce bone production when implanted into ectopic sites [53,54]. Interestingly, Emdogain has been reported to inhibit the ectopic osteogenic capacity of dentin [53].…”
Section: Discussionmentioning
confidence: 99%